Human development and land tenure in Brazil - Alexandre Arbex Valadares; Fernando Gaiger da Silveira; Nikolas Camargo de Pirani (International Policy Centre for Inclusive Growth (IPC-IG), 2017)
The perpetuation of profound socio-economic inequalities between the countryside and the city, inscribed in the differences between their respective quality of life indicators, allows us to state that rural and urban environments still have distinct social realities, despite territorial contiguity and the rising intercommunication between these spaces. This study proposes to investigate how living conditions and human development in the rural environment might be linked to a structural characteristic of the Brazilian countryside: the high concentration of land ownership. [...]
Keywords: 330; human development; land tenure; Brazil